2005
DOI: 10.1007/s10814-005-0809-4
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Social Complexity in the Chibchan World of Southern Central America and Northern Colombia, AD 300?600

Abstract: The societies of southern Central America and northern South America, a region historically occupied by Chibchan-speaking peoples, have long been acknowledged as valuable sources of information on chiefdoms and other forms of prestate social organization. Most studies, however, have focused on chiefdoms that are known ethnographically or ethnohistorically with an emphasis on the sixteenth century and the immediate precontact period. This paper reviews archaeological evidence from an earlier period in an attemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
11

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 60 publications
2
20
0
11
Order By: Relevance
“…In recent decades, a sound understanding of the Chibchan language family has been established (Constenla Umaña 1981, 1991, Quesada 2007 and complemented by archaeological studies (Lange & Stone 1984, Bray 2003, Hoopes & Fonseca Z 2003, Hoopes 2005) that, taken together, indicate Chibchan-speaking populations originated in Mesoamerica, spreading to northern South America in prehistoric times. Studies of mtDNA diversity amongst modern Mesoamerican Chibchan-speakers have found they are characterized by high frequencies of haplogroup A (>65%), markedly lower frequencies of B (20-30%), very low frequencies of D, and absence of C (Santos & Barrantes 1994, Torroni et al 1994, Batista et al 1995, Kolman & Bermingham 1997.…”
Section: Chibchan-speaking Populations Of Mesoamerica and Northern Somentioning
confidence: 99%
“…In recent decades, a sound understanding of the Chibchan language family has been established (Constenla Umaña 1981, 1991, Quesada 2007 and complemented by archaeological studies (Lange & Stone 1984, Bray 2003, Hoopes & Fonseca Z 2003, Hoopes 2005) that, taken together, indicate Chibchan-speaking populations originated in Mesoamerica, spreading to northern South America in prehistoric times. Studies of mtDNA diversity amongst modern Mesoamerican Chibchan-speakers have found they are characterized by high frequencies of haplogroup A (>65%), markedly lower frequencies of B (20-30%), very low frequencies of D, and absence of C (Santos & Barrantes 1994, Torroni et al 1994, Batista et al 1995, Kolman & Bermingham 1997.…”
Section: Chibchan-speaking Populations Of Mesoamerica and Northern Somentioning
confidence: 99%
“…The ties founded on networks and exchange form one of the most common bases for unequal power relations and are especially important in small-scale and middle-range societies (Bayman, 1999(Bayman, , 2002Brumfiel and Earle, 1987;Cobb, 1993Cobb, , 1996Hoopes, 2005;Junker, 1993;Quesada, 1998;Saitta, 1999;Spielmann, 1998Spielmann, , 2002Wells, 1999). Important to the understanding of exchange and unequal power relations in small-scale and middlerange societies are what have variously been termed "prestige," "wealth," "sumptuary," or "exotic" goods (see Goldstein, 2000), goods that are highly valued for their rarity, are nonlocal, and are usually "costly" because of the skills and knowledge required to create and obtain them.…”
Section: Exchange and Craft Production In The Political Economymentioning
confidence: 99%
“…Several anthropomorphic Axe-God Theme pendants from the site of Las Huacas, Pacific Northwest, Costa Rica (Hartman, 1907), dated based on ceramic associations to ca. A.D. 300-500 (Hoopes, 2005), bear these same attributes; one of these ( Figure 4c) bears the double-tufted head crest also seen with the Mercocha pendant. In fact, this double-tufted head crest is also seen in another pendant from Mercocha, only this time it is a representation of an Avian Axe-God Theme (Figure 4d).…”
mentioning
confidence: 82%